The American Presidency’s Discretionary Power in the Adoption of Bilateral and Multilateral Environmental Agreements: The Reagan Administration in the 1980s - Ludovica Di Gregorio (USAbroad, 2024)
The power that the United States has been able to exert in international environmental agreements has not always worked towards establishing a better global environment mainly due to a clash of national and international interests. Through the analysis of the Reagan Administration (1981-1989), this essay aims to show how the presidential administrative capacities on the national level can lead to unexpected consequences on the international level. In this respect, this essay will focus on two important topics—the Montreal Protocol and the U.S.-Canada bilateral relations—which led to remarkably different outcomes, albeit starting from similar premises.